Somatropin in short bowel syndrome: opening the door to trophic factor use. Issue 1 (January 2006) - DiBaise, John K
The management of short bowel syndrome is complex and frequently requires parenteral nutrition support to ensure the sufficient administration of nutrients and fluids. Despite advances in the provision of parenteral nutrition, this mode of nutritional support carries with it significant risks to the patient, impairs quality of life and is very costly. Since intestinal adaptation plays a key role in the successful management of patients with short bowel syndrome, recent investigations have focused on the use of trophic substances to enhance intestinal adaptation and increase the absorptive function of the remaining gut. Published reports from a number of studies conducted in animal models and humans with short bowel syndrome evaluating the efficacy of recombinant human growth hormone (i.e., somatropin) in this regard have demonstrated conflicting findings. However, substantial methodologic differences among the studies limit definitive conclusions regarding the benefit of this therapy on intestinal adaptation. Subsequent studies in short bowel syndrome patients have focused on the ability of recombinant human growth hormone to allow reduction in parenteral nutrition requirements. In a recent randomized, controlled trial of recombinant human growth hormone, glutamine and a specialized oral diet, treatment with recombinant human growth hormone 0.1 mg/kg/day for 4 weeks resulted in significant reductions in parenteral nutrition requirements compared with the control group. These results led to the approval of somatropin by the US Food and Drug Administration for use in patients with short bowel syndrome receiving specialized nutrition support. Somatropin appears to be well tolerated with generally manageable side effects. Fluid retention, gastrointestinal symptoms and injection site reactions occur commonly; however, serious adverse effects are uncommon. Optimal clinical benefits appear to be achieved when somatropin is administered in combination with a specialized oral diet and, if possible, oral glutamine. It should be used under the guidance of clinicians experienced in the management of short bowel syndrome, with the expectation that these patients need to be monitored closely during and after its use. Further study is needed regarding the persistence of effect after treatment, optimal dose and length of administration for subsequent courses of treatment with somatropin as well as its safety, long-term benefit and use in the pediatric and geriatric populations.